2016
DOI: 10.1186/s13027-016-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Relapses of primary cutaneous anaplastic large-cell lymphoma in a female immunocompetent patient with persistent chlamydophila pneumoniae and human herpesvirus 8 infection

Abstract: BackgroundWe have previously reported the case of an immunocompetent female patient with a primary cutaneous CD30+ anaplastic large-cell lymphoma (PCALCL) located on her upper right eyelid characterized by the presence of a concurrent active infection by C. pneumoniae and Human herpesvirus 8 (HHV8). This finding suggested for the first time a possible association of C. pneumoniae and/or HHV8 infection, or both together, with PCALCL pathogenesis in non-immunocompromised and HIV-negative subjects. The subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The association between Th 1 response impairment and C. pneumoniae infection may be also supported by increased incidence of bacterial DNA in patients with atopic dermatitis (12.5%) (Th 2 cytokines pattern) vs. psoriatic patients (2.5%) (Th 1 cytokines pattern) and healthy controls (0%) (immunocompetent individuals). C. pneumoniae DNA was detected only in one skin biopsy in our study group, in accordance with the results of German and Italian investigators, who not detected bacterial in the skin biopsies from MF/SS patients, and confirm that C. pneumoniae infection could not be estimated as a primary event in the pathogenesis of CTCL, in spite of Casselli et al case describing skin presence of Chlamydia spp (and HHV8) in all recurrences of CD30+CTCL as well as in routine control blood samples [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…The association between Th 1 response impairment and C. pneumoniae infection may be also supported by increased incidence of bacterial DNA in patients with atopic dermatitis (12.5%) (Th 2 cytokines pattern) vs. psoriatic patients (2.5%) (Th 1 cytokines pattern) and healthy controls (0%) (immunocompetent individuals). C. pneumoniae DNA was detected only in one skin biopsy in our study group, in accordance with the results of German and Italian investigators, who not detected bacterial in the skin biopsies from MF/SS patients, and confirm that C. pneumoniae infection could not be estimated as a primary event in the pathogenesis of CTCL, in spite of Casselli et al case describing skin presence of Chlamydia spp (and HHV8) in all recurrences of CD30+CTCL as well as in routine control blood samples [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…Clinical disease linked to this bacterium includes keratoconjunctivitis (3), and urogenital infections and infertility (31,32). Associations between different herpesviruses and Chlamydia infection have also been described epidemiologically for humans and cats (33)(34)(35)(36). In vitro coinfection studies of Chlamydia trachomatis and human herpesviruses have indicated complicated virus-host-bacterium interactions, including virus-induced chlamydial persistence (37,38) and an increase in viral entry into normally nonsusceptible cells infected with Chlamydia (37).…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydophila pneumoniae DNA was detected only in one skin biopsy in our study group, in accordance with the results of German and Italian investigators, who did not detect any bacterial DNA in skin biopsies from MF/SS patients, and confirm that C. pneumoniae infection could not be estimated as a primary triggering factor in the pathogenesis of CTCL, in spite of Casselli et al who had described skin presence of Chlamydia spp. (and HHV8) in all recurrences of CD30+CTCL as well as in routine control blood samples [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%